THE EFFECT OF CUCUMBER JUICE THERAPY ON BLOOD PRESSURE REDUCTION IN PATIENTS IN INTERNAL DISEASE POLICY - Mahruri Mahruri; Reka Julia Utama; Mohd. Rizal Fahmi Adha (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Hypertension is a health problem in all parts of the world and is one of the main risk factors for cardiovascular disease. The factors that influence hypertension are genetics, age, gender, ethnicity, obesity, lifestyle, and food intake. The therapy that is often used by the community is cucumber which is very good for consumption for people with hypertension. The purpose of this study was to identify the effect of cucumber juice therapy on reducing blood pressure in patients at the Internal Medicine Polyclinic of the Meranti Islands District Hospital. This research was conducted at the Internal Medicine Poly Hospital of Meranti Islands Regency, the sampling technique using accidental sampling technique, with the number of respondents 30 people. The research design used is a quasi-experimental design (one group pretest–posttest). Data collection tools are GEA brand sphygmomanometer, stethoscope, observation sheet and SOP on how to make cucumber juice which were analyzed by univariate and bivariate dependent t-test (paired t test). The results of this study found that there was an effect of cucumber juice therapy on reducing blood pressure in patients at the Internal Medicine Clinic at the Meranti Islands District Hospital both systole and diastole (p=0.000). It is hoped that this will become the basis for the Meranti Islands District Hospital to be a reference so that cucumber juice therapy can be a complementary intervention and a room SOP is made for this intervention.